THE EVALUATION OF THE COLONIZATION AND BIOFILM FORMATION CAPACITY OF THE CANDIDA SPECIES ISOLATED FROM DENTURE WEARER PATIENTS - (:unkn) unknown (My University, 2019)
Aim: Candida species, although being a member of theoral flora, may exhibit pathological features under certainconditions. The aim of this study was to determine thedistribution and biofilm production of Candida speciesthat were isolated from denture related stomatitis (DRS)patients and to compare with healthy subjects.Materials and Methods: The 56 non-smoker,systemically healthy, maxillary removable denture wearersubjects included in this study and diagnosed asDRS(N=27) and healthy(N=29). Samples from the palatalmucosal surface of patients were collected by sterileswabs during 20 seconds. Cultivation and selectiveisolation of Candida species were performed onCHROMagar (CHROMagar®Candida, CHROMagar, Paris,France) at 37ºC for 2 days. Isolated Candida specieswere identified with API ID 32 C (bioMérieux®, France).Biofilm formation by Candida species were determined bya visual tube method.Results: The prevalence of the yeasts in the healthygroup was found to be 37.94%, while in the DRS group itwas 100% (p<0.001). The isolation rate of C. albicans inpatients with DRS significantly higher (p<0.001). Biofilmformation was observed in a total of 37 oral yeastisolates, 9 isolates from healthy den- ture wearers and 28isolates from DRS patients. The number of C. albicansand C. glabrata isolates showing biofilm formation abilityin the DRS group was significantly higher than thehealthy group (p<0.05).Conclusions: Within the limitations of this study, ourresults suggest that Candida species play a major role onthe development of DRS. While C. albicans was the mostisolated species in DRS, C. glabrata was as important asC. albicans on the pathogenesis of DRS.

Amaç: Candida türleri, oral floranın doğal üyesi ol- makla birlikte, belirli koşullar altında patolojik özellikler sergileyebilir. Bu çalışmanın amacı, protez stomatiti (PS) olan hastalardan ve protez kullanan sağlıklı bireylerden elde edilen Candida türlerinin dağılımını ve biyofilm üretime kapasitelerini karşılaştırmaktır. Gereç ve Yöntem: Sigara içmeyen, sistemik olarak sağlıklı, maksiller tam damak protez kullanan 56 kişi bu çalışmaya dahil edildi. Katılımcılar PS (N = 27) ve sağlıklı (N = 29) olmak üzere gruplandırıldı. Hastaların palatal mukoza yüzeyinde 20 saniye boyunca steril swablar gezdirilerek sürüntü örnekleri elde edildi. Candida türlerinin kültivasyon ve seçici izolasyonu 2 gün boyunca 37°C'de CHROMagar (CHROMagar® Candida, CHROMagar, Paris, Fransa) besiyerinde ger- çekleştirildi. Ġzole edilen Candida türlerinin identifikas- yonu API ID 32 C (bioMérieux®, Fransa) ile gerçekleş- tirildi. Candida türlerinin biyofilm oluşturma potansi- yelleri görsel tüp yöntemi ile saptandı. Bulgular: Sağlıklı gruptaki mayaların prevalansı % 37.94 iken, PS grubunda % 100'dü (p <0.001). PS'li hastalarda C. albicans'ın izolasyon oranı anlamlı dere- cede daha yüksekti (p <0.001). Sağlıklı katılımcılardaki 9 PS katılımcılardaki 28 izolatta biyofilm oluşumu gözlendi. PS grubunda biyofilm oluşumunu gösteren C. albicans ve C. glabrata izolatlarının sayısı sağlıklı gruba göre anlamlı olarak yüksekti (p <0.05). Sonuç: Bu çalışmanın sınırları dahilinde, sonuçlarımız Candida türlerinin PS'nin gelişiminde önemli bir rol oynadığını göstermektedir. C. albicans, PS'de en sık izole edilen tür olsa da C. glabrata da PS'nin patoge- nezinde C. albicans kadar önemlidir.
HAREKETLİ PROTEZ KULLANAN HASTALARDA KANDİDA TÜRLERİNİN KOLONİZASYONUNUN VE BİYOFİLM OLUŞTURMA KAPASİTELERİNİN DEĞERLENDİRİLMESİ
Keywords: Diş Hekimliği